Protective Effect of γ-Irradiation Against Hypochlorous Acid-Induced Haemolysis in Human Erythrocytes - Idolo Tedesco; Carmela Spagnuolo; Maria Russo; Roberta Iannitti; Annunziata Nappo; Gian Luigi Russo (Dose-Response, 2013)
Radiations may trigger protective response within a threshold of doses applied. Exposures above an upper threshold are generally detrimental, while exposures below a lower threshold may or may not increase risks for health. We recently reported that a cellular protective response occurs in interventional cardiologists to counteract the oxidative damage caused by radiation. Here, we demonstrated in an in vitro model represented by whole blood of healthy donors γ-irradiated with 220–440 mGy, that haemolysis of erythrocytes induced by hypochlorous acid was reduced by 40%. The protection triggered by γ-radiations made erythrocytes more resistant to oxidative insult caused by hypochlorous acid which was induced 3 h after irradiation and involved biochemical changes in the synthesis and turnover of glutathione. Overall, the biochemical remodelling induced by exposure to γ-radiations might contribute to generate new guidelines in professionally exposed workers.